Functional Polymers in Sensors and Actuators: Fabrication and Analysis - Kaynak, Akif; Zolfagharian, Ali (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Recent advances in the fabrication techniques have enabled the production of different types of polymer sensors and actuators that can be utilized in a wide range of applications, such as soft robotics, biomedical, smart textiles and energy harvesting. Functional polymers possess dynamic physical and chemical properties, which make them suitable candidates for sensing and actuating tasks in response to external stimuli, such as radiation, temperature, chemical reaction, external force, magnetic and electric fields. This book focuses on the recent advancements in the modeling and analysis of functional polymer systems.